2019
DOI: 10.1016/j.ejvssr.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Extracranial Internal Carotid Artery Aneurysms in a Patient with Marfan Syndrome: Case Report and Review of the Literature

Abstract: IntroductionAneurysms of the extracranial carotid artery are rare. They are often asymptomatic but can lead to disabling stroke. This report describes a case of bilateral internal carotid artery aneurysms in a patient with Marfan syndrome.ReportA 65 year old woman with Marfan syndrome presented with an asymptomatic swelling in the right anterior triangle of the neck. Imaging revealed bilateral extracranial fusiform internal carotid artery aneurysms. Staged open repair was performed. The right side was repaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Although with favorable outcomes in both short and long term, open surgery is associated with high occurrence of cranial nerve damage. 11 On the contrary, covered stent in endovascular therapy can immediately exclude blood flow from aneurysms, thereby minimizing complications associated with rupture or local compression. 32,33,[41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Although with favorable outcomes in both short and long term, open surgery is associated with high occurrence of cranial nerve damage. 11 On the contrary, covered stent in endovascular therapy can immediately exclude blood flow from aneurysms, thereby minimizing complications associated with rupture or local compression. 32,33,[41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that up to 13% of patients with EICAA exhibit bilateral EICAAs. Additionally, multiple synchronous aneurysms, specifically intracranial ones, have been documented in approximately 15%–20% of patients diagnosed with EICAA 10–14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations